Synthesis and Catalytic Properties of Novel Ruthenacarboranes Based on nido-[5-Me-7,8-C2B9H10]2− and nido-[5,6-Me2-7,8-C2B9H9]2− Dicarbollide Ligands - Ivan D. Grishin (MDPI AG, 2021)
The effect of methyl substituents in the lower belt of dicarbollide ligands on the redox potential of ruthenacarboranes based thereof, as well as the ability of the metallacarboranes obtained to catalyze radical polymerization with atom transfer were studied. For this purpose, a new approach to the synthesis of closo-ruthenacarboranes based on substituted dicarbollide ligands was developed and six new complexes 3,3-(Ph2P(CH2)4PPh2)-3-H-3-Cl-9-Me-12-X-closo-3,1,2-RuC2B9H9, 3,3,8-(Ph2P(CH2)4PPh-μ-(C6H4-o))-3-Cl-9-Me-12-X-closo-3,1,2-RuC2B9H8 and 3,3,4,8-(Ph2P(CH2)4P-μ-(C6H4-o)2)-3-Cl-9-Me-9-X-closo-3,1,2-RuC2B9H7 (X = H, Me) were synthetized and characterized by single crystal X-ray diffraction, NMR and ESR spectroscopy and MALDI TOF mass-spectrometry. Comparison of the values of the redox potentials of the synthesized ruthenium complexes in 1,2-dichloroethane with the values previously found for the corresponding ruthenacarboranes based on the parent dicarbollide anion showed that the introduction of methyl substituents into the carborane cage led to a decrease in the redox potentials of the complexes, which made them more preferable catalysts for ATRP. Test experiments on the polymerization of MMA showed that the synthesized ruthenacarboranes were effective catalysts for ATRP, the most active being the complex with two methyl groups and two ortho-phenylenecycloboronated fragments.